Faktor-Faktor Yang Mempengaruhi Keberhasilan Usaha Mustahik Pada Program Zakat Produktif Di Baznas Prov. Sumatera Utara - Alghifari, Dimas; Amini, Nur Rahmah (Yayasan Rahmat Islamiyah, 2023)
This study aims to analyze the facthors that influence the success of mustahik businesses in giving productive zakat given by the Provincial Baznas. North Sumatra. The research method used is a quantitative approach with logistic regression analysis techniques. The sample in the study consisted of 40 people, the results obtained from calculations using the slovin formula. The results of this study indicate that: simultaneous and partial tests show all the variable. Intermediate influence on business success mustahik obtain significant result.